Optimalisasi Penggunaan Layanan Sistem Informasi Desa Bakbakan - Indraswari, Ni Made Dwi; Wijaya, I Nyoman Yudi Anggara; Paramitha, A.A. Istri Ita (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The role of information technology in village development is very important, Bakbakan Village is a village located in Gianyar regency, Bali province. Currently, Bakbakan Village has a village information system using OpenSID. However, the obstacle experienced by Bakbakan Village is that the community has not been able to use OpenSID to conduct self-service. In addition, another obstacle faced by Bakbakan Village is that access to village profile information is not fully accessible online.Based on the problems faced by Bakbakan Village, therefore the village government and also the Gianyar Regency Community and Village Empowerment Office are collaborating with Primakara University through the Merdeka Belajar-Kampus Merdeka (MBKM) program with the Final Project scheme.